(untitled) (Palimpsesto, 2021)
The purpose of this article is to examine the weekly Chile Hoy, specifically the political commentaries of the members of its editorial committee, who were recognized marxist intellectuals coming from the social sciences and linked to the Centro de Estudios Socioeconómicos (CESO) of the Universidad de Chile. This group analyzed the possibilities of the socialist project from a critical, propositional and conjunctural perspective, highlighting the tensions between the political strategy of the Salvador Allende government and the emergence of popular power. This action is seen as an act of verbalization of the political and legitimization strategy that allowed them to position themselves in the debate on the Chilean revolution.